HISTORICAL AND CULTURAL COMMONALITIES OF IRAN WITH THE COUNTRIES OF THE CAUCASUS (CASE STUDY OF ARMENIA AND GEORGIA) - Motamednia Masoumeh; Nouri Choreti Mehdi (Многоязычие в образовательном пространстве)
Throughout history, in order to achieve its strategic goals in the peripheral regions, Iran has repeatedly attacked the land of the Caucasus. During the Achaemenid period, Georgia and Armenia came under the rule of Iran. During the Seleucid era, the Caucasus was divided into several tributary principalities, and with the rise of Tirdad, the Parthian prince in Armenia, the Parthian dynasty began in this region. Then the Sasanians and the Parthians invaded these areas. Until the Qajar era, these areas were part of Iran, but in 1228, with the conclusion of the Golestan treaty, a large part of them was taken over by the Russians, and after that, the Turkmenchay treaty separated these territories from other areas. All in all, the contacts between peoples led to the emergence of various commonalities in these areas. Since ancient times, the Caucasus was considered the connecting link between Asia and Europe, and its commonality with Iranian civilisation was so great that there are still many signs of community in the history, culture, and language of the countries of this area. They are evident in Nowruz rituals, religious events, cultural occasions, general lifestyle and even the type of clothing. Iran’s attention to the Caucasus region, especially the social, linguistic and historical interactions in this region are considered in the comparative context. Therefore, in this article, we are looking for the answer to the question concerning the links and commonalities created by Iran’s historical encounters with the Caucasus, especially in Armenia and Georgia.